The C5a/C5aR1 Axis Contributes to the Pathogenesis of Acute Cystitis Through Enhancement of Adhesion and Colonization of Uropathogenic E. coli - Wu, Kun-Yi; Cao, Bo; Wang, Chun-Xuan; Yang, Xue-Ling; Zhao, Shu-Juan; Diao, Teng-Yue; Lin, Li-Rong; Zhao, Guo-Xiu; Zhou, Wuding; Yang, Ju-Rong; Li, Ke (Frontiers in Cellular and Infection Microbiology, 2022)
Our previous work using a murine model of pyelonephritis demonstrated that C5a/C5aR1 axis plays a pathogenic role in acute kidney infection. In this study, we report that C5a/C5aR1 axis also plays a pathogenic role in acute bladder infection. C5aR1 deficient mice had reduced bladder bacterial load and attenuated bladder tissue injury, which is associated with reduced expression of terminal α-mannosyl residues (Man) (a potential ligand for type 1 fimbriae of E. coli) at luminal surface of bladder epithelium and reduced early bacterial colonization of the bladder. In vitro, C5a stimulation enhanced mannose expression in and facilitated bacterial adhesion/colonization to human bladder epithelial cells. C5a stimulation also upregulated activation of ERK1/2 and NF-κB signaling and gene expression of proinflammatory cytokines (i.e., Il6, Il1b, Cxcl1, Ccl2) in the epithelial cells, which could drive pro-inflammatory responses leading to tissue injury. Administration of C5aR1 antagonist effectively reduced bladder bacterial load and tissue injury. Thus, our findings demonstrate a previously unknown pathogenic role for C5a/C5aR1 axis in bladder infection and suggest that C5a/C5aR1 axis-mediated upregulation of Man expression, enhancement of bacterial adhesion/colonization and excessive inflammatory responses contribute to acute bladder infection. These findings improve our understanding of the pathogenesis of bladder infection with therapeutic implications for UTI.